Transformasi dan Inovasi Manajemen Pendidikan Islam - Abdur Rouf (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
In this era of global reform, a renewal and improvement of the quality of society is necessary in order to ensure decent changes, both in terms of education, social and cultural rights. The changes as a result of the development of science and technology is rapidly increasing, which in turn forms the characteristic of competitive environment. So there is no place in society without competition. Competition is the principle of a new life, because it is the condition for the better world. Transformation and innovation is urgently needed nowadays. Hence, it will bring significant changes as well as reform in Islamic education management.